2020
DOI: 10.1590/s1984-29612020062
|View full text |Cite
|
Sign up to set email alerts
|

Survey of vector-borne and nematode parasites involved in the etiology of anemic syndrome in sheep from Southern Brazil

Abstract: Although anemia has been historically linked to Haemonchus contortus infection, other infectious agents, such as hemotropic mycoplasmas and tick-borne disease pathogens, may also lead to anemic crisis in sheep. This study has aimed to investigate infections related to anemia in a sheep herd from Bandeirantes City, Paraná State, southern Brazil. Seven out of forty-two (16.6%; 95% CI: 8.32–30.6%) sheep were positive for hemoplasmas by a PCR targeting the 16S rRNA gene and all tested negative for A. marginale/A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…(5′-GGACAGAATTTACCTGACAAGG-3′), described by Mongruel et al (2020). The amplification mixture contained 1× PCR buffer, 1.5 mM of MgCl 2 , 0.2 mM of each dNTP, 0.4 mM of each primer, 2.5 U of Taq Platinum DNA Polymerase (Life Technologies ™ ), 5 μl of DNA template, and ultrapure water q.s.p 25 μl.…”
Section: Cpcr For Hms Based On the 23s Rrna Genementioning
confidence: 99%
“…(5′-GGACAGAATTTACCTGACAAGG-3′), described by Mongruel et al (2020). The amplification mixture contained 1× PCR buffer, 1.5 mM of MgCl 2 , 0.2 mM of each dNTP, 0.4 mM of each primer, 2.5 U of Taq Platinum DNA Polymerase (Life Technologies ™ ), 5 μl of DNA template, and ultrapure water q.s.p 25 μl.…”
Section: Cpcr For Hms Based On the 23s Rrna Genementioning
confidence: 99%
“…The gapdh gene was consistently amplified in all ring-tailed coati (Barker et al, 2011;Pontarolo et al, 2021;Valente et al, 2020;Vieira et al, 2021). On this pattern, the 23S rRNA sequences amplified in the present study showed only 94.3%-94.1% identity to 'Ca.…”
Section: Resultsmentioning
confidence: 49%
“…of the 16S rRNA gene of haemoplasmas (Hoelzle et al, 2011;Machado et al, 2017). Ring-tailed coatis' DNA samples that showed to be positive in the cPCR assay based on the 16S rRNA were submitted to genus-specific cPCR assays targeting fragments of the 23S rRNA (800 pb) (Mongruel et al, 2020) and RNaseP (170 bp) genes (Compton et al, 2012) of haemoplasmas. Nuclease-free water and Mycoplasma ovis DNA obtained from a naturally infected goat (Capra hircus) blood sample were used as negative and positive controls, respectively, in both cPCR assays.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, DNA samples were screened for haemotropic mycoplasmas using a PCR assay targeting a fragment (∼900 bp) of the 16S rRNA gene of haemoplasmas (Hoelzle et al., 2011; Machado et al., 2017). Porcupine DNA samples that tested positive in the PCR assay based on the 16S rRNA gene were subjected to a genus‐specific PCR assay targeting a fragment (800 pb) of the 23S rRNA gene of haemoplasmas (Mongruel et al., 2020). Mycoplasma ovis DNA obtained from a naturally infected goat (Machado et al., 2017) and nuclease‐free water were used as positive and negative controls, respectively.…”
Section: Methodsmentioning
confidence: 99%